Phytotoxicity of different antibiotics to rice and stress alleviation upon application of organic amendments. (November 2020) - Mukhtar, Ayesha; Manzoor, Maria; Gul, Iram; Zafar, Rabeea; Jamil, Hira Imam; Niazi, Adnan Khan; Ali, Muhammad Arif; Park, Tae Jung; Arshad, Muhammad
Abstract: Extensive use of antibiotic results in significant antibiotics pollution in the environment. Main objective of this study was to gain insight into potential impacts of antibiotics on plant physiological growth and nutritional composition, and stress alleviation through application of different organic amendments. Effects of five antibiotics (ciprofloxacin, levofloxacin, ofloxacin, amoxicillin and ampicillin) were observed in the presence of three organic amendments (rice husk, farmyard manure and poultry litter) with rice ( Oryza sativa L.) as a model plant. Organic amendments were mixed with soil (@ 5 g kg −1 ) and after three weeks, antibiotics were applied (@10 mg kg −1 ) and plants were allowed to grow for four months. After which plants were harvested and physical growth parameters (root/shoot length, biomass) and nutritional composition (grain protein content, carbohydrates, phosphorous and iron) were monitored. It was observed that germination rate, seedling root/shoot length, seedling biomass and vigor index were negatively impacted. The application of organic amendments alleviated antibiotic stress on seedling dry biomass, length and vigor index by 1.8–, 3.1– and 2.5–folds, respectively as compared to the antibiotic controls. Concentrations of phosphorous, iron, carbohydrates and proteins were decreased by 5.3–, 1.3–, 1.4– and 1.6–folds upon application of antibiotics. Rice husk was the most effective treatment in case of physical growth parameters and alleviating antibiotics' induced genotoxicity. Whereas, poultry litter had the highest positive effect on nutritional composition of plants. In general, the application of organic amendments alleviated the phytotoxicity as well as genotoxicity in plants under antibiotics stress. Graphical abstract: Image 1 Highlights: Potential of organic amendments for antibiotic stress alleviation in rice was tested. Antibiotics showed significant phytotoxicity and genotoxicity in rice plants. Rice husk alleviated stress on physiological growth parameters and genotoxicity. Poultry litter improved nutritional composition of rice along with stress alleviation.